A welfare comparison of life-cycle investment strategies for Turkey - Khodzhimatov, Ravshanbek. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
We perform an in-depth welfare comparison of the most common life-cycle investment strategies provided by retirement funds or suggested by classical portfolio theory in the case of households in Turkey. To perform our benchmarking, we construct heterogeneous agents who work and invest throughout their lifetime, using parameters calibrated from the historical data. We ﬁnd that to households with upper-to-middle income, individually customized portfolios result in considerable welfare gains, while “off-the-shelf” life-cycle portfolio allocations perform better for households with lower income. We also show that life-cycle investment options outperform “ﬁxed over the lifetime” options. Finally, we ﬁnd that risk-averse individuals with volatile wages, can maximize their welfare by investing in housing as suggested by Munk (2016).
Keywords: Investments -- Econometric models.; Welfare economics -- Turkey.